2016
DOI: 10.1159/000443875
|View full text |Cite
|
Sign up to set email alerts
|

Newborn Resuscitation Training Programmes Reduce Early Neonatal Mortality

Abstract: Background: Substantial health care resources are expended on standardised formal neonatal resuscitation training (SFNRT) programmes, but their effectiveness has not been proven. Objectives: To determine whether SFNRT programmes reduce neonatal mortality and morbidity, improve acquisition and retention of knowledge and skills, or change teamwork and resuscitation behaviour. Methods: We searched CENTRAL, MEDLINE, PREMEDLINE, EMBASE, CINAHL, Web of Science and the Oxford Database of Perinatal Trials, ongoing tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 61 publications
1
51
0
Order By: Relevance
“…Of these deaths, 2.6 million are classified as stillbirths and 2.9 million occur during the neonatal period (1). Training in neonatal resuscitation has the potential to significantly reduce both intrapartumrelated stillbirths and neonatal mortality (3,4). Training in neonatal resuscitation has the potential to significantly reduce both intrapartumrelated stillbirths and neonatal mortality (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Of these deaths, 2.6 million are classified as stillbirths and 2.9 million occur during the neonatal period (1). Training in neonatal resuscitation has the potential to significantly reduce both intrapartumrelated stillbirths and neonatal mortality (3,4). Training in neonatal resuscitation has the potential to significantly reduce both intrapartumrelated stillbirths and neonatal mortality (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Bellad et al [23] showed that HBB training was not associated with consistent improvements in mortality rates among all neonates ≥1,500 g in India and Kenya. The implementation of quality improvement interventions and low-dose/ high-frequency training including in situ simulation may facilitate the transfer of new knowledge/skills into clinical practice, thereby reducing perinatal mortality in Tanzania, Nepal and Sudan [7,15,24].…”
Section: Discussionmentioning
confidence: 99%
“…Neonatal resuscitation has gathered considerable attention, with the Neonatal Resuscitation Program (NRP) [4] and Helping Babies Breathe (HBB) [5] being taught in over 100 countries. Despite increasing information on resuscitation training in low-resource settings [6,7], the most efficient and effective ways for health care workers to acquire and maintain neonatal resuscitation skills are still undefined [8]. In addition, incorrect, ineffective or dangerous forms of practice are actually widespread [1,9].…”
mentioning
confidence: 99%
“…A systematic review calculated that if every birth was attended by someone who had undergone standardised formal neonatal training, 140 000 lives would be saved each year (3). This huge figure shows that major reductions in neonatal mortality are possible in those parts of the world with the highest perinatal mortalities, such as sub-Saharan Africa.…”
Section: Helping Babies Breathe Can Reduce Deaths With the Right Combmentioning
confidence: 99%
“…Other studies have been reassuring about morbidity rates, as they have shown that babies who needed resuscitation from low-income and middle-income countries did not have an excess of neurological or developmental morbidity at 12 months of age (9,10). More research, however, is needed to understand the long-term effect of resuscitation programmes in the context of babies with birth asphyxia and subsequent neonatal encephalopathy (3).…”
Section: Helping Babies Breathe Can Reduce Deaths With the Right Combmentioning
confidence: 99%